Isovalent sulfur substitution to induce a simultaneous increase in the effective mass and weighted mobility of a p-type Bi-Sb-Te alloy: an approach to enhance the thermoelectric performance over a wide temperature range. (15th February 2021) - Lee, Kyu Hyoung; Kim, Hyun-Sik; Kim, Minyoung; Roh, Jong Wook; Lim, Jae-Hong; Kim, Won Joong; Kim, Sang-il; Lee, Wooyoung
Abstracts: A significant obstacle to obtaining enhanced thermoelectric performance (defined by a thermoelectric figure of merit, zT ) in commercial p -type Bi-Sb-Te alloys is bipolar transport originating from their intrinsic narrow-band-gap semiconducting characteristics. Cation-site doping is commonly used to suppress the bipolar conduction. However, zT enhancement occurs often only at elevated temperatures since the electronic thermal conductivity mainly increases at low temperatures due to the increase of hole concentration. Herein, the substitution of isovalent S ions in the anion Te-site of Bi-Sb-Te is explored to obtain a high zT over a wide temperature range by simultaneously increasing the density-of-states effective mass and weighted mobility. The zT of Bi0.49 Cu0.01 Sb1.5 Te3 is enhanced by ~10 % for all measured temperatures, and the average zT increases beyond 1.0 between 300 and 520 K, benefitting from the synergetic control of band structure and deformation potential via S substitution. Graphical abstracts: Image, graphical abstract